The Mediterranean-dietary approaches to stop hypertension diet intervention for neurodegenerative delay (MIND) diet: a bibliometric analysis - Dai, Linxiong; Lin, Xiaoxiao; Wang, Shuai; Gao, Yue; He, Fei (Frontiers in Nutrition, 2024)
The MIND diet is a healthy dietary pattern that has some benefits for many health outcomes. Our study aims to conduct a bibliometric analysis of the MIND diet, identifying leading edges and hotspots to provide a reference for future research. The research on the MIND diet was gathered from the Web of Science Core Collection (WOSCC) database. For bibliometric analysis, VOSviewer 1.6.16 and the WOSCC Online Analysis Platform were utilized. In total, this comprehensive investigation encompassed 171 documents in the field of the MIND diet. The publications are globally distributed, with contributions from 953 authors across 362 institutions in 37 countries/regions, and published in 94 journals. The United States leads with 72 publications, and Iran and the People’s Republic of China also show notable engagement with 28 and 19 publications, respectively. Rush University stands out with 21 publications, followed by Harvard University and Tehran University of Medical Sciences, demonstrating their substantial contributions to this field. Martha Clare Morris is a key figure with 10 publications, alongside Klodian Dhana and Puja Agarwal, each contributing 9 publications, highlighting their influence in the MIND diet research. The journal “Nutrients” is a major publication venue with 20 related articles, followed by “Frontiers in Nutrition” and “Journal of Nutrition Health Aging,” reflecting their crucial roles in advancing knowledge about the MIND diet. The first high-cited publication was published in Alzheimers & Dementia and conducted by Martha Clare Morris, which focuses on the MIND diet’s relationship with Alzheimer’s disease prevention and cognitive decline and emphasizes the diet’s neuroprotective potential, highlighting how even moderate adherence can substantially reduce Alzheimer’s risk and slow cognitive decline. In conclusion, this is the first comprehensive bibliometric study that quantitatively and qualitatively analyzed the publications in the field of the MIND diet. The MIND diet may be a promising dietary pattern for dementia. However, the current evidence is restricted and highlights the urgency and necessity of further research to investigate the efficacy of this diet for cognitive function. In addition, the MIND diet may have some benefits for other health outcomes, including CVDs, cancer, and diabetes. The number of studies in the field of the MIND diet is limited. More studies are needed, and will give us more knowledge about the MIND diet to improve human health, especially for dementia.